DAMPAK NILAI TUKAR DAN RISK-BASED BANK RATING TERHADAP PREDIKSI KONDISI PERBANKAN INDONESIA - Diana Kanya Prasidha (Quantitative Economics Journal, 2015)
Model predictions to asses the problematic conditions in banking sectors need to be developed. It because by knowing early of systemic risks condition, policymakers can take anticipation actions. In this study, the financial ratios used are RiskProfile, Good Corporate Governance, Earning, and Capital (RGEC) rating based approach. The risk profile is proxied by the Non Performing Loan (NPL) which represented by the Net Open Position (PDN) for market risk, and Loan to Deposit Ratio (LDR) for liquidity risk. Meanwhile, good corporate governance aspect is not investigated since the aspect is more qualitative. Then, the profitability aspect proxied by the Return on Asset (ROA) and Net Interest Margin (NIM), while the capital aspect proxied by the Capital Adequacy Ratio (CAR). In this study added one macroeconomic variables, namely the Exchange Rates. The study was conducted in 2009-2013 to predict and analyze the performance of the Indonesian banking sector, particularly for Private National Banks which are the most susceptible to problematic conditions. Using the logistic regression model, the results showed that the variables of NPL, PDN, ROA, and Exchange Rates are significantly effect on the probability of occurrence of the condition of troubled banks.